2017
DOI: 10.1016/j.biomaterials.2016.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Myosin phosphorylation on stress fibers predicts contact guidance behavior across diverse breast cancer cells

Abstract: During cancer progression the extracellular matrix is remodeled, forming aligned collagen fibers that proceed radially from the tumor, resulting in invasion. We have recently shown that different invasive breast cancer cells respond to epitaxially grown, aligned collagen fibrils differently. This article develops insight into why these cells differ in their contact guidance fidelity. Small changes in contractility or adhesion dramatically alter directional persistence on aligned collagen fibrils, while migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 77 publications
(105 reference statements)
2
42
1
Order By: Relevance
“…MDA-MB-231 cells robustly engage in contact guidance and take migration steps primarily in directions along the long axis of the collagen fibrils over the first 10 h. 52,53 However, we observed that for longer times (12–24 h), cells pull (using contractility) and potentially degrade (using MMP activity) the collagen fibrils to such a large extent that the cells detach. This detachment phenotype is robust and is not seen in MTLn3 cells.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…MDA-MB-231 cells robustly engage in contact guidance and take migration steps primarily in directions along the long axis of the collagen fibrils over the first 10 h. 52,53 However, we observed that for longer times (12–24 h), cells pull (using contractility) and potentially degrade (using MMP activity) the collagen fibrils to such a large extent that the cells detach. This detachment phenotype is robust and is not seen in MTLn3 cells.…”
Section: Resultsmentioning
confidence: 74%
“…52 In addition, turning cell contractility either up or down can correspondingly alter contact guidance efficiency in a dose dependent manner. 53 MDA-MB-231 cells move on these substrates along the collagen fibrils (Fig. 1b).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations